Critical Sources of Aerodynamic Resistance in a Medium Distance Urban Train: a CFD approach - Andrés Tabares (Universidad de San Buenaventura, 2013)
In this article, the aerodynamic behavior of a commuter train operating at average speeds is evaluated, by means of computational fluid dynamics; the main goal is to identify the main aerodynamic drag sources. The study consist of two phases; the first one is the aerodynamic analysis of the current train using certain mesh parameters and the turbulence model – to obtain a real condition of operation, with this analysis was obtained the total power consumption corresponding to the value of the aerodynamic drag thrown by the simulation process. These results were qualitatively compared with experimental data in order to validate the simulation process. The second part is the identification and analysis of the main aerodynamic drag zones that the Metro system generate in its interaction with the air, to make a preliminary evaluation of a few modifications that allowed the reduction in the drag in these critical